Análise do programa de fortalecimento da qualidade da atenção primária em saúde em municípios de região de fronteira do Paraná - Santiago, Alexandra Urnau (2021)
Primary Care has constituted itself as the main gateway for the health services provided by the National Health System (SUS). The state of Paraná, with the objective of enhancing the services at this level of attention (primary care), has enacted the Qualification Program of Primary Care in Health Services (APSUS), establishing protocols and conventions to organize the work process, the guarantee of the users’ and the workers’ safety, the processes' management and the improvement of the population health indicators. The cities that have adhered to this Program, have been thoroughly assessed and monitored concerning the items that comprehend the structure, the work process and the health indicators. The following research is characterized as exploratory-descriptive with a mixed approach, having as its main objective to analyze the results of the implementation of the Qualification Program of Primary Care in Health Services (APSUS) in cities of frontier region from Paraná that have received any type of label or seal from the Quality Program. The Data Collection was carried out through semi-structured interviews with nurses, coordinators of Primary Health Care and municipal health secretaries from seven cities. The data collected were analyzed based on the Policy Cycle proposal. The research sample is constituted by: municipal health secretaries (05), Primary Health Coordinator (01) and Nurses from the Health Centers (8), totalizing 14 participants from the cities belonging to the 8, 9º and 20º Health District. The data collection was carried out in the period from October 2020 to January 2021 and comprehends information from the interviewees profile, their qualifications and the composition of the teams, the research object, analyses of the main health indicators, implementation of the Qualification Program of Primary Care in the managers' and nurses' perspective, the attendance to foreigners and the pandemic influences in the work process of Primary Care. The results, both in the managers’ and the nurses’ perspective, have indicated important changes in: (i) work process, (ii) information registration, (iii) increase of the relationship with the community and (iv) contribution of tutoring processes in the support and planning of the team's actions. Some initial difficulties in the adherence and engagement of the team with the Program's objectives and premises were noted, as well as some reluctance from the population in accepting the implemented changes and the negative effect in the team with the decision of the state government to interrupt the program. When analyzing the health indicators, it was demonstrated that no significant changes were found in most of the cities in the analyzed period. Concerning the attendance to foreigners, although all the cities have demonstrated this attendance, there are a series of restrictions and is mostly held in cases of emergency and urgency. The main influences of the pandemic were also put forward when considering the work process of the health teams, and the discontinuation of the program in this major health crisis, with possible consequences to the population health, especially in the control of chronical diseases. It is concluded that evaluating and assessing policies and programs is of great importance, to point out the advances and the fragilities arising from changes, even when they are intrinsic to the health team's work.